2015
DOI: 10.1016/j.rmed.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine profiles of patients with interstitial lung disease associated with anti-CADM-140/MDA5 antibody positive amyopathic dermatomyositis

Abstract: These results confirmed that anti-CADM-140/MDA5 antibody levels could predict outcomes of ADM-ILD. Relationship analyses suggested that CX3CL1 might be involved in the pathogenesis of anti-CADM-140/MDA5 antibody positive ADM-ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Dr. Hirata has received consulting fees, speaking fees, and/or honoraria from AbbVie, Asahi Kasei Pharma, Asahi Kasei Medical, Astellas Pharma, in the study if they were diagnosed as having definite, probable, or possible DM or CADM with ILD-without immunosuppressive treatment-before admission to one of the registered hospitals. Serum anti-MDA-5 was detected by immunoprecipitation (IP) assay using 35 S-labeled HeLa cells and confirmed by anti-MDA-5 enzyme-linked immunosorbent assay (ELISA; Mesacup). Patients with the following conditions were excluded: active tuberculosis, active hepatitis B virus infection, cancer, and patients <16 years of age.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dr. Hirata has received consulting fees, speaking fees, and/or honoraria from AbbVie, Asahi Kasei Pharma, Asahi Kasei Medical, Astellas Pharma, in the study if they were diagnosed as having definite, probable, or possible DM or CADM with ILD-without immunosuppressive treatment-before admission to one of the registered hospitals. Serum anti-MDA-5 was detected by immunoprecipitation (IP) assay using 35 S-labeled HeLa cells and confirmed by anti-MDA-5 enzyme-linked immunosorbent assay (ELISA; Mesacup). Patients with the following conditions were excluded: active tuberculosis, active hepatitis B virus infection, cancer, and patients <16 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the IgG-coated Sepharose was washed, then suspended in 400 ml of IP buffer for polypeptide studies. HeLa cells (2 × 10 7 ) in 100 ml of methionine-free medium were labeled with 18.5 MBq of 35 S-methionine (Perkin Elmer) overnight at 37°C; they were then sonicated in 2 ml of IP buffer, and the supernatant was recovered by centrifugation. Antibody-coated Sepharose beads were mixed with 100 ml of 35 S-methionine-labeled HeLa cell extracts, then rotated at 4°C for 2 hours.…”
Section: Detection Of Anti-mda-5 Antibody In Ip Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we did not evaluate changes to other inflammatory cytokines, including serum interleukin (IL)-6, IL-8, IL-10, IL-18, interferon (IFN)-α, IFN-γ, macrophage colony-stimulating factor, CX3CL1, or messenger RNA levels of CD11b in circulating neutrophils, which have also been indicated to represent pathogenic factors for RPIP. [20][21][22][23][24][25] Activation of monocytes and macrophages through these factors has been suggested to underlie the pathophysiology of anti-MDA5 Ab-positive DM patients. 20,25 Further studies should be conducted to elucidate whether removal of these factors with TPE contributes to disease control.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed the relationship between the titres of anti-MDA-5 autoantibodies and each cytokine/GF protein concentration before immunosuppressive treatment to find the highest Spearman's rank correlation coefficients in CX3CL1 (r = 0.8897, P < 0.001) [4]. Serum cytokine/GF protein in this case demonstrated that the concentrations of FGF-2, IL-1ra, IL-17A, IP-10, and MCP-1 decreased after addition of MMF as well as CX3CL1.…”
Section: Reduced Cytokines By Mmf In Adm-ildmentioning
confidence: 99%